2018
DOI: 10.3348/kjr.2018.19.6.1179
|View full text |Cite
|
Sign up to set email alerts
|

Size-Specific Dose Estimation In the Korean Lung Cancer Screening Project: Does a 32-cm Diameter Phantom Represent a Standard-Sized Patient in Korean Population?

Abstract: ObjectiveThe purposes of this study were to evaluate size-specific dose estimate (SSDE) of low-dose CT (LDCT) in the Korean Lung Cancer Screening (K-LUCAS) project and to determine whether CT protocols from Western countries are appropriate for lung cancer screening in Korea.Materials and MethodsFor participants (n = 256, four institutions) of K-LUCAS pilot study, volume CT dose index (CTDIvol) using a 32-cm diameter reference phantom was compared with SSDE, which was recalculated from CTDIvol using size-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
4
5
0
Order By: Relevance
“…A previous study had observed that when the automated exposure control (AEC) system was deployed, both CTDIvol and SSDE values were higher in large-sized subjects than those who were standard-sized. When the AEC system was turned off, there seems to be no significant difference between the radiation doses in different subject sizes [12]. This observation was aligned with in this study where the AEC was deployed.…”
Section: Discussionsupporting
confidence: 86%
“…A previous study had observed that when the automated exposure control (AEC) system was deployed, both CTDIvol and SSDE values were higher in large-sized subjects than those who were standard-sized. When the AEC system was turned off, there seems to be no significant difference between the radiation doses in different subject sizes [12]. This observation was aligned with in this study where the AEC was deployed.…”
Section: Discussionsupporting
confidence: 86%
“…A previous study had observed that when the automated exposure control (AEC) system was deployed, both CTDIvol and SSDE values were higher in large-sized subjects than those who were standard-sized. When the AEC system was turned off, there seems to be no significant difference between the radiation doses in different subject sizes [13]. This observation was aligned with this study where the AEC was deployed.…”
Section: Discussionsupporting
confidence: 84%
“…A previous study had observed that when the automated exposure control (AEC) system was deployed, both CTDIvol and SSDE values were higher in large-sized subjects than those who were standard-sized. When the AEC system was turned off, there seems to be no significant difference between the radiation doses in different subject sizes (Kim et al, 2018). This observation was aligned with this study, where the AEC was deployed.…”
Section: Patient Characteristic and Radiation Dosesupporting
confidence: 85%